A Study on Semiconductor Memory Cells Using CMOS- Technologies in Digital Electronics - Rohit Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The CMOS technology is known for low threshold voltage high density and high performance. The electronic circuit or components density has increased daily in a single chip by employing VLSI design. The power consumption going to low and operating frequency achieved higher through VLSI technology. In this article, we included a brief review on digital electronic memory cell and future technology. We have mainly focused flash memory devices such as Static Random-access memory (SRAM), dynamic Random-access memory (DRAM) and Flip- flop. RAM is a very powerful components for personal computer, mobile and any electronic gadgets. The development of RAM and flip-flop in the form of memory is very important because its impacts on the performance of the programs in personal computer (PC). Now a days, all the research and development as well as normal work have been dependent on the PC performance. The speed of the PC depends on RAM and flash memory used in PC configurations. This is the main reason to study and analyzed the digital memory cell, especially RAM and flip-flop. These are various applications in VLSI digital clock system, baths, registers, microprocessors, etc., and very low power consumptions.